Application and perspectives of nanomaterials in boron neutron capture therapy of tumors - Xiaomei Li; Puyi He; Yujie Wei; Caihao Qu; Futian Tang; Yumin Li (Cancer Nanotechnology)
Abstract Boron neutron capture therapy (BNCT) is a two-step targeted radiotherapy technique, which selectively delivers 10B atoms to tumor tissues, leading to selective tumor destruction through thermal neutron irradiation. BNCT, which utilizes boron agents, such as BPA and BSH, has demonstrated promising results in tumor treatment. However, it still faces several challenges, including insufficient tumor targeting, rapid in vivo metabolism, and high doses due to poor solubility. To address these challenges, nanotechnology-based boron drug delivery systems have emerged as a crucial strategy to enhance the therapeutic efficacy of BNCT. This paper thus summarizes the respective drug-carrying modes and provides an evaluation of the advantages and disadvantages of inorganic nanomaterials (e.g., gold nanoparticles, boron nanoparticles, carbon nanoparticles, silica nanoparticles, magnetic nanoparticles), organic nanomaterials (e.g., liposomes, polymer nanoparticles, dendritic macromolecules, micelles), and natural nanomaterials. In addition, we discuss pressing issues and future research directions regarding the use of nanomaterials as boron drug carriers, with the aim of offering valuable insights into the advancement of these materials in both basic and clinical research application.